Forecasting human resource needs for shaping Veterinary and Animal Husbandry sector in Amritkaal - TRIPATHI, HEMA; AGRAWAL, RAKESH CHANDRA; TRIPATHI, BHUPENDRA NATH; PATHAK, HIMANSHU (The Indian Journal of Animal Sciences, 2024)
The present study provides an in-depth exploration of the demand and supply landscape for human resources within India’s Veterinary and Animal Husbandry (VAH) sector, aiming to identify the current and future challenges in meeting the workforce needs. It assesses the demand for veterinary professionals, taking into account various influencing factors such as the sector’s historical growth trends, the emerging roles, challenges posed by technological advancements and the expected integration of various sectors. Simultaneously, the supply side is scrutinized through an analysis of educational output, considering both the potential increase in the number of training institutions and the anticipated fluctuations in graduation rates due to policy changes or other external factors. The core objective of this paper is to shed light on the significant discrepancy between the available supply of veterinary graduates and the burgeoning demand within the sector. This gap is underscored by the study’s projection of a gradual narrowing over the coming decades, attributed to strategic increases in educational capacity. However, the analysis suggests that substantial efforts in expanding the number of veterinary colleges will be essential to align the supply with the projected demand effectively. This assessment underlines the critical need for a concerted and strategic approach to bolster the sector’s human resource base, ensuring its capacity to meet future challenges.